ADAR1: a central regulator of dsRNA sensing in host-virus interactions - Liu, Congnuan; Choi, Younho (Frontiers in Immunology, 2026)
Adenosine deaminase acting on RNA 1 (ADAR1) is a key regulator of RNA homeostasis and innate immunity through its adenosine-to-inosine (A-to-I) editing of double-stranded RNAs (dsRNAs). By editing endogenous dsRNAs, ADAR1 prevents inappropriate activation of RNA sensors such as PKR, RIG-I, and MDA5, thereby maintaining immune tolerance to self RNA. However, growing evidence indicates that this essential immunomodulatory function of ADAR1 can be exploited by viruses to facilitate infection. Many viruses leverage ADAR1 to suppress RLR- and PKR-mediated signaling, dampen type I interferon responses, and promote viral replication-highlighting a prominent proviral role for ADAR1. Conversely, ADAR1 can also exert antiviral effects, including hyper-editing of viral genomes, disruption of viral RNA structures, and modulation of host antiviral signaling pathways. Thus, ADAR1 acts as a context-dependent regulator of virus-host interactions, functioning both as a guardian against aberrant immune activation and as a host factor co-opted by viruses to establish productive infection. Understanding how viruses manipulate ADAR1 and how ADAR1 differentially impacts PKR and RIG-I/MDA5 pathways will advance our knowledge of viral immune evasion mechanisms and may inform new therapeutic strategies. This review summarizes current insights into the antiviral and proviral roles of ADAR1 during viral infection, with emphasis on viral strategies that finetune ADAR1 activity to shape infection outcomes.